Age at first molar emergence in Pan troglodytes verus and variation in the timing of molar emergence among free-living chimpanzees. Issue 145 (August 2020) - Kelley, Jay; Schwartz, Gary T.; Smith, Tanya M.
Abstract: Age at lower first molar (M1 ) emergence is a commonly used proxy for inferring life-history scheduling in fossil primates, but its utility is dependent on knowing to what extent extant populations vary in this datum and how this variation correlates with the scheduling of life-history variables. Here, we address the first of these issues among extant chimpanzees. While age at M1 emergence has been documented in several live individuals from the Kanyawara population of Pan troglodytes schweinfurthii in Uganda, it has been estimated for only one individual of Pan troglodytes verus, based on a deceased animal from the Taï Forest in Côte d'Ivoire. To further explore interpopulation variation in this variable in chimpanzees, and using dental histology, we calculated ages at death for two wild-shot individuals of P. t. verus with erupting M1, both collected in Liberia during the mid-1950s, and estimated ages at M1 emergence from the ages at death. The overall range for these two individuals is ∼4.2–4.6 yr, compared with an age of ∼3.7 yr for the individual from the Taï Forest, and <2.5–3.3 yr for the several individuals of P. t. schweinfurthii. While the absolute range of ∼2 yr in these samples combined is little greater than in captive chimpanzees, the disparity between the samples of P. t. schweinfurthii and P. t. verus is striking, although it cannot be determined if this disparity represents a subspecies difference or simply population differences expressed in two different subspecies. While life-history data are unavailable for the population to which the Liberian chimpanzees belonged, the difference in M1 emergence ages between these individuals and those from Kanyawara still suggests caution when attempting even broad life-history inference in fossil apes and hominins based on age at M1 emergence.